2015
DOI: 10.5194/acp-15-7999-2015
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory photochemical processing of aqueous aerosols: formation and degradation of dicarboxylic acids, oxocarboxylic acids and α-dicarbonyls

Abstract: Abstract. To better understand the photochemical processing of dicarboxylic acids and related polar compounds, we conducted batch UV irradiation experiments on two types of aerosol samples collected from India, which represent anthropogenic (AA) and biogenic (BA) aerosols, for time periods of 0.5 to 120 h. The irradiated samples were analyzed for molecular compositions of diacids, oxoacids and α-dicarbonyls. The results show that photochemical degradation of oxalic (C 2 ), malonic (C 3 ) and other C 8 -C 12 di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 63 publications
1
48
0
Order By: Relevance
“…2b), which are the major organic compounds produced by the oxidation of anthropogenic cyclohexene and methylenecyclohexane (Hamilton et al, 2006;Muller et al, 2007). Although C 5 and C 6 diacids are the ozonolysis products in smog chamber studies, Pavuluri et al (2015) recently proposed that C 5 and C 6 are produced by photochemical processing of aqueous aerosols from a laboratory study. Such a molecular distri- Table 1 for abbreviations.…”
Section: Concentrations and Molecular Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b), which are the major organic compounds produced by the oxidation of anthropogenic cyclohexene and methylenecyclohexane (Hamilton et al, 2006;Muller et al, 2007). Although C 5 and C 6 diacids are the ozonolysis products in smog chamber studies, Pavuluri et al (2015) recently proposed that C 5 and C 6 are produced by photochemical processing of aqueous aerosols from a laboratory study. Such a molecular distri- Table 1 for abbreviations.…”
Section: Concentrations and Molecular Distributionsmentioning
confidence: 99%
“…Indeed, from a model study it has been proposed that photochemical oxidation of isoprene and subsequent partitioning of water-soluble photooxidation products into the aqueous phase is a predominant formation pathway of oxalic acid (Myriokefalitakis et al, 2011). Most of the previous studies of diacids and other organic compounds in aerosols have been conducted at ground surface; however, only a few aircraft observations have been conducted over the arctic region (Talbot et al, 1992), the western North Pacific (Narukawa et al, 1999), the western rim of the Pacific Ocean (Kawamura et al, 2003), the coastal marine stratocumulus and cumulus clouds over USA (Crahan et al, 2004;Sorooshian et al, 2013Sorooshian et al, , 2007aWonaschuetz et al, 2012;Prabhakar et al, 2014) and over inland agricultural and urban areas in the western USA (Sorooshian et al, 2015). These aircraft experiments have revealed that water-soluble diacids may be produced by the photochemical oxidation of anthropogenic organic compounds in the atmosphere and thus play an important role in controlling the chemical and physical properties of OA in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of organics in atmospheric waters are considered to be an important process that results in high abundance of oxalic (C 2 ) acid (Pavuluri et al 2015b). Such processing of aerosols is significant under strong solar radiation and high humid environment and thus enhances the loading of short-chain diacids and the fraction of total diacids and related compounds to OA (Yang et al 2008, Pavuluri et al 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of organics in atmospheric waters are considered to be an important process that results in high abundance of oxalic (C 2 ) acid (Pavuluri et al 2015b). Such processing of aerosols is significant under strong solar radiation and high humid environment and thus enhances the loading of short-chain diacids and the fraction of total diacids and related compounds to OA (Yang et al 2008, Pavuluri et al 2015b. Generally, in terrestrial or marine aerosols, C 2 acid was often found as the most abundant species of diacids, followed by malonic (C 3 ) or C 4 acids, whereas in polar aerosols, C 4 acid found to be higher occasionally than that of C 2 , particularly in the samples collected under overcast conditions with brume events Ikushima 1993, Kawamura et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation